TRAINING OF QUALITY ASSURANCE SPECIALISTS FOR THE ENTERPRISES OF PETROCHEMICAL COMPLEX IN CONDITIONS OF THE FORMATION OF THE TECHNICAL REGULATION SYSTEM - Vasilii G. Ivanov; Elena V. Priymak; Il’dus A. Biktagirov (Высшее образование в России)
The article touches upon the problem of shortage and even absence of experts, capable to solve the questions concerning technical regulation of quality and safety of production in the conditions of the Customs Union, Uniform economic space and the WTO. Kazan National Research Technological University has elaborated special skill raising programs in the sphere of organization, functioning, and administration of the system of technical regulation adapted to the requirements of the Customs Union and WTO. The authors came to a conclusion of the necessity of introducing into curricular of economic and engineering universities anew economicdiscipline -“Economics, trade policy and WTO law and practice”.